2021
DOI: 10.1007/s10615-021-00788-x
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Beyond: A Prototype for Remote/Virtual Social Work Field Placement

Abstract: The COVID-19 pandemic necessitated an abrupt conclusion of field placement for social work interns at a comprehensive cancer center. In response to social distancing requirements, social workers, but not interns, were granted access to work remotely. Virtual programming became necessary to meet the interns' remaining educational requirements and provided an opportunity for proper termination from the program. This article will delineate the program redesign for oncology social work interns using remote/virtual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…They felt disconnected from the field and their peers, which influenced their learning process, which is inconsistent with the study (deJonge et al, 2020;Mitchell et al, 2021). Conversely, few studies have shown positive aspects in students' engagement with service users, mutual aid, and fostering a sense of connection among participants (Azeez, 2015;De Fries et al, 2021;Morley & Clarke, 2020;Papouli et al, 2020;Pink et al, 2021;Wilke et al, 2009).…”
Section: Discussionmentioning
confidence: 84%
“…They felt disconnected from the field and their peers, which influenced their learning process, which is inconsistent with the study (deJonge et al, 2020;Mitchell et al, 2021). Conversely, few studies have shown positive aspects in students' engagement with service users, mutual aid, and fostering a sense of connection among participants (Azeez, 2015;De Fries et al, 2021;Morley & Clarke, 2020;Papouli et al, 2020;Pink et al, 2021;Wilke et al, 2009).…”
Section: Discussionmentioning
confidence: 84%
“…A recommendation to value the concerns of both the opposing views of hour reduction would be to keep the reduction, yet changing the tasks to ensure that the time the students have is used for high-quality tasks and functions, as meaningful learning is the priority. With the very real possibilities of future disasters, training for virtual platforms will be an ongoing need (Mitchell et al, 2021). Online training opportunities, for both field instructors (Ayala et al, 2014) and students (Kourgiantakis & Lee, 2020), have demonstrable benefits to field education.…”
Section: Discussionmentioning
confidence: 99%
“…In an article written by Mitchell et al (2021), the necessity and experience of training MSW students on RSWP was presented. The authors describe the effects of COVID-19 on the social work internship experience of social work oncology interns (e.g., practicum students) and the program redesign that occurred as a result of the pandemic in an attempt to transition to RSWP.…”
Section: Introductionmentioning
confidence: 99%